Control of a Cooperative Transportation System with Two Car-Like Mobile Robots (A Path-Following Feedback Control Method for Two Manipulating Points on a Carrier) - YAMAGUCHI, Hiroaki; SUZUKI, Ryuichi; KAWAKAMI, Atsushi (Nihon Kikai Gakkai rombunshuu. C hen, 2012)
This paper presents a novel path-following feedback control method of two manipulating points defined on a carrier of a cooperative transportation system with two car-like mobile robots. Since the path-following feedback control method previously presented by the authors causes the first car-like mobile robot to follow a path and causes the orientation of the carrier relative to that of the tangent of the path to be constant, the carrier is swung around during the transportation in cases where the curvature of the path is high, increasing the risk of overturning the load on the carrier. To resolve this problem, this paper presents the novel path-following feedback control method which causes both of the two manipulating points on the carrier to follow the path. This method makes it possible to design the motion of the carrier as that of a segment between the two manipulating points. The kinematical equation of the transportation system is converted into a chained form in a coordinate system where the path is one coordinate axis and a straight line perpendicular to the tangent of the path is the other coordinate axis. The convergence of the position of one manipulating point into its desired position on the path is guaranteed by the linear control theory, and that of the position of the other manipulating point is guaranteed by the Lyapunov 's second method and the Lyapunov function is designed based on the chained form. The validity of the novel path-following feedback control method is verified experimentally.